A Swedish validation of the Berlin Numeracy Test. Issue 2 (8th January 2015) - Lindskog, Marcus; Kerimi, Neda; Winman, Anders; Juslin, Peter
<x xml:space="preserve">Abstract</x> Recent research has highlighted the importance of considering an individual's level of numeracy, that is their numerical abilities, in a vast variety of judgment and decision making tasks. To accurately evaluate the influence of numeracy requires good and valid measures of the construct. In the present study we validate a Swedish version of the Berlin Numeracy Test (Cokely, Galesic, Schulz, Ghazal & Garcia‐Retamero, 2012). The validation was carried out on both a student sample and a sample representative of the Swedish population. The Swedish BNT showed sound psychometrical properties in both samples. Further, in both samples the BNT had satisfactory convergent and discriminant validity when correlating with other measures of numeracy, while not being significantly related to measures of personality. With respect to predictive validity the results indicated divergent patterns in the two samples. In the student sample, participants scoring highest on the BNT outperformed those in the other three levels, which did not differ in performance. In contrast, in the population sample participants scoring lowest on the BNT performed worse than those in the other three levels, which did not differ in performance. Taken together, however, the results suggest that the Swedish version of the BNT should be considered a valid measure of numeracy in both Swedish student and population representative samples.